2018
DOI: 10.1088/2057-1976/aac19b
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric modulated arc therapy applied to synchronous bilateral breast cancer radiotherapy: dosimetric study on deep inspiration breath hold versus free breathing set up

Abstract: Aim. The purpose of this planning report is to compare dosimetric results of deep inspiration breath hold (DIBH) and free breathing (FB) set up in patients with synchronous bilateral breast cancer (SBBC) treated with adjuvant radiotherapy. Material and methods. Fourteen patients with early stage bilateral breast cancer were treated with breast conservative surgery. Bilateral breast planning treatment volume (PTV) and organs at risk (OARs) were delineated for DIBH and FB datasets on the planning computed tomogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“… 5 , 6 , 8 , 9 , 10 , 13 Respiratory management with DIBH or respiratory gating also reduces the dose to the heart and lungs. 11 Two clinical series of adjuvant photon radiation therapy for SBBC reported good oncologic outcomes and low rates of radiation-associated lung toxic effects. Twenty-one patients were treated with tomotherapy and assessed with pulmonary function tests and high-resolution CT scans.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 5 , 6 , 8 , 9 , 10 , 13 Respiratory management with DIBH or respiratory gating also reduces the dose to the heart and lungs. 11 Two clinical series of adjuvant photon radiation therapy for SBBC reported good oncologic outcomes and low rates of radiation-associated lung toxic effects. Twenty-one patients were treated with tomotherapy and assessed with pulmonary function tests and high-resolution CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…We selected VMAT as a gold standard comparison to IMPT in this study because multiple planning studies have shown that VMAT and hybrid techniques achieve superior normal tissue avoidance compared to 3D techniques 5,6,[8][9][10]13 . Respiratory management with DIBH or respiratory gating also reduces dose to the heart and lungs 11 . Two clinical series of adjuvant photon radiotherapy for SBBC reported good oncologic outcomes and low rates of radiation-associated lung toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study also showed a similar trend with 3DCRT+IMRT and 3DCRT+VMAT hybrid plans. Subramanian et al, (2016) Gaudino et al, (2018) compared VMAT to SBBC RT in deep inspiration breath-hold (DIBH) versus free-breathing set up. While it was reported that the DIBH method can able to reduce the dose to the heart, LAD, and lungs, this practice might not be achievable for all patients.…”
Section: Discussionmentioning
confidence: 99%